Fernpendeln mit welchem Verkehrsmittel? Fallstudie aus der Region Rhein-Main zu Situation und Reagibilität in der Verkehrsmittelnutzung. - Manz, Wilko; Wittowsky, Dirk (Deutscher Verkehrs-Verl., 2007)
Die individuelle Entscheidung, "wie" und "womit" eine physische Raumüberwindung ausgeführt wird, ist bei vielen Verkehrsteilnehmern von alltäglichen Verhaltensroutinen geprägt. Gerade Prozesse der Verkehrsmittelwahl zu regelmäßig aufgesuchten Zielen wie dem Arbeits- oder Ausbildungsplatz unterliegen bei Fernpendlern häufig gefestigten Grundsatzentscheidungen, die das Ergebnis eines individuellen Optimierungsprozesses widerspiegeln. difu

The public dispute on the climate change sensitised traffic participants for a responsible exposure to commuters' mobility. Particularly, long-distance commuters, who make up about one quarter of total kilometers commuted, should be gained to use transport means that have less impact on the environment. This initial situation gives reason to do scientific research on the phenomenon of long-distance commuting. By means of a telephone survey in the region of Limburg, long-distance commuters were interviewed about their mobility behaviour in detail. Most of the commuters apparently made their modal choice by considering all other transport means. Especially, for journeys with a travel distance of more than 60 km a share in the public transport up to 40 % can be observed. Since the temporal and financial burden for long-distance commutes is enormous, travellers have a positive attitude towards new travel alternatives. difu
Keywords: Verkehr; Verkehrsmittelwahl; Entscheidungsgrundlage; Berufspendler; Befragung; Einstellung; Fallstudie; Fernpendler; Arbeitsweg; Empirische Untersuchung